Alta pressão hidrostática como ferramenta de seleção direcionada em S. cerevisiae para produção de etanol 2g pela casca de coco verde - Santos, Luiza Favarato (2019)
The green coconut shell is a pollutant residue of the environment generated to tons in Brazil and that brings several environmental problems in its disposal. Therefore, using it for the production of renewable energy is an important sustainable solution for the mitigation of the environmental impact and for the generation of energy. Yeast Saccharomyces cerevisiae represents one of the microorganisms most used in the fermentation industries for the production of biofuels from lignocellulolytic residues. There are already on the market strains of this yeast capable of degrading lignocellulolytic residues, which have been developed to increase the yield of the process, making it feasible financially on an industrial scale. The high pressure hydrostatic (HHP) is a tool that simulates three types of different stresses in the yeast: the ethyl, the thermal and the oxidative, which are very common in fermentation dornas. In addition, studies have shown that fermentation occurs more rapidly when the yeast is under HHP. Therefore, HHP can be used as a targeted selection tool to obtain a strain with higher fermentation capacity and greater resistance to fermentation stresses, increasing the yield of the process. The aim of this work was to apply a selective pressure to the S. cerevisiae strain G2-104 using high hydrostatic pressure in order to obtain a strain with a higher fermentation capacity in green coconut shell culture medium, to increase the yield of the second generation ethanol production process.